The Psychometric Properties of the Norwegian version of Five to Fifteen - Hysing, Mari; Bøe, Tormod (PsykTestBarn, 2013)
Description: (FTF; Five To Fifteen) is a questionnaire assessing problems in children in the areas of motor function, attention/executive function, language, memory, learning, social skills, internalizing and externalizing behavior problems. The questionnaire was developed by a Nordic expert group in 2014. Only professionals such as medical doctors, psychologists, or educators with a corresponding level of education, who have received test administration training, are qualified to administer the instrument. Basic psychometric competence is required. Literature search: The literature search did not identify any Norwegian studies that met the inclusion criteria. Three Scandinavian studies were included, including three validation studies and one comparison between FTF and Child Behavior Checklist (CBCL). Psychometrics: Results from the Scandinavian studies indicate excellent internal consistency reliability, acceptable to good reliability, and good to excellent test-retest reliability for the main scales. Part of the test discriminates among different diagnostic groups, and FTF scores are correlated with scores on tests such as the WISC-II and NEPSY. Conclusion: The psychometric properties of the FTF have not been not documented in Norwegian studies. Scandinavian studies indicate good psychometric properties. When using the FTF, one should keep in mind that the norms are based on Finnish and Swedish samples.